Delayed cell cycle pathway modulation facilitates recovery after spinal cord injury - Wu, Junfang (Landes Bioscience, 2012)
Traumatic spinal cord injury (SCI) causes tissue loss and associated neurological dysfunction through mechanical damage and secondary biochemical and physiological responses. We have previously described the pathobiological role of cell cycle pathways following rat contusion SCI by examining the effects of early intrathecal cell cycle inhibitor treatment initiation or gene knockout on secondary injury. Here, we delineate changes in cell cycle pathway activation following SCI and examine the effects of delayed (24 h) systemic administration of flavopiridol, an inhibitor of major cyclin-dependent kinases (CDKs), on functional recovery and histopathology in a rat SCI contusion model. Immunoblot analysis demonstrated a marked upregulation of cell cycle-related proteins, including pRb, cyclin D1, CDK4, E2F1 and PCNA, at various time points following SCI, along with downregulation of the endogenous CDK inhibitor p27. Treatment with flavopiridol reduced induction of cell cycle proteins and increased p27 expression in the injured spinal cord. Functional recovery was significantly improved after SCI from day 7 through day 28. Treatment significantly reduced lesion volume and the number of Iba-1(+) microglia in the preserved tissue and increased the myelinated area of spared white matter as well as the number of CC1(+) oligodendrocytes. Furthermore, flavopiridol attenuated expression of Iba-1 and glactin-3, associated with microglial activation and astrocytic reactivity by reduction of GFAP, NG2, and CHL1 expression. Our current study supports the role of cell cycle activation in the pathophysiology of SCI and by using a clinically relevant treatment model, provides further support for the therapeutic potential of cell cycle inhibitors in the treatment of human SCI.